Fuzzy Fixed Point Theorem for Some Types of Fuzzy Jungck Contractive Mappings In Hilbert Space - Ahmed, Buthainah A.A.; Dheyab, Manar Falih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper, developed Jungck contractive mappings into fuzzy Jungck contractive and proved fuzzy fixed point for some types of generalize fuzzy Jungck contractive mappings.